Influence of various gauge lengths, root spacing and root numbers on root tensile properties of herbaceous plants - Zhang, Chaobo; Ma, Xiaoyu; Liu, Yating; Jiang, Jing (Penerbit Universiti Kebangsaan Malaysia, 2021)
The mechanical properties of root system play an important role in soil reinforcement by plants. Root tensile properties are affected by many factors. It is necessary to explore the mechanical properties of root system and the influencing factors. In this study, tensile tests were conducted on roots of Kochia scoparia (L.) Schrad and Artemisia sacrorum Ledeb to study root tensile properties, including maximum tensile force, tensile strength and elastic modulus under the three factors, gauge length (50, 100, 150, and 200 mm), root spacing (0, 1, and 2 cm) and root number (single root, double roots, and triple roots). The results showed that the maximum tensile force, tensile strength, and elastic modulus of the roots decreased with increasing gauge length in power functions. Under 100 mm gauge length, the maximum tensile force, tensile strength and elastic modulus decreased with increasing root spacing, but the effect of root spacing considered in this study on the maximum tensile force and tensile strength was not significant. Besides, with increasing root number, the maximum tensile force increased, tensile strength, and elastic modulus decreased. These findings stretched our understanding of the relationship between gauge length, root spacing and root number on root tensile characteristics, and provided the necessary data basis for root tensile properties and soil reinforcement by plants.